2008
DOI: 10.1111/j.1440-1819.2008.01822.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic effect of nicotine on serotonin transporter mRNA in the raphe nucleus of rats: Reversal by co‐administration of bupropion

Abstract: Aim: Epidemiologic studies suggest the existence of a biological link between nicotine withdrawal and depression. To investigate the neuronal mechanisms of the precipitation of depression during smoking cessation, an animal model of nicotine withdrawal was used, and the expression of serotonin transporter (5HTT), abnormality of which is implicated in the pathogenesis of depression, was investigated. The effect of co-administration of bupropion, which has been clinically shown to ameliorate nicotine withdrawal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…Prior studies have reported mixed effects of chronic nicotine exposure on the density of 5-HTTs, thus regulating the amount of synaptic serotonin available for 5-HT 3 receptors. For example, Semba and Wakuta (2008) reported a reduction in the density of 5-HTTs in the rat brain whilst two other studies reported an elevation in 5-HTTs (Awtry and Werling, 2003; Slotkin and Seidler, 2010). On the other hand, Staley et al (2001) reported an elevation 5-HTTs in the human brain, and in human platelets they were reported to be reduced (Patkar et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have reported mixed effects of chronic nicotine exposure on the density of 5-HTTs, thus regulating the amount of synaptic serotonin available for 5-HT 3 receptors. For example, Semba and Wakuta (2008) reported a reduction in the density of 5-HTTs in the rat brain whilst two other studies reported an elevation in 5-HTTs (Awtry and Werling, 2003; Slotkin and Seidler, 2010). On the other hand, Staley et al (2001) reported an elevation 5-HTTs in the human brain, and in human platelets they were reported to be reduced (Patkar et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this discrepancy is unclear, as the groups are similar for age, gender distribution, Fagerstöm scores and withdrawal durations. Possible explanations include inter-group differences of the effects of chronic nicotine exposure on other neuromodulatory systems such as dopamine and serotonin 52, 53 , as well as Brain-derived neurotrophic factor (BDNF) levels 54 , which are shown to have an impact on stimulation-induced plasticity 5557 . Varenicline administration probably activated α 4 β 2 nAChRs, which are assumed to be desensitized by chronic nicotine exposure 58, 59 , thus facilitating intracellular calcium influx and therefore enabling either LTP or LTD-like after-effects after tDCS and PAS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many concerns exist about the risks of using a potentially hazardous chemical to treat AD patients (Baldinger and Schroeder, 1995). Similarly, literature surveying the effect of nicotine on depressive-like behavior is ambivalent with some preclinical studies reporting decreased (Djuric et al, 1999; Semba and Wakuta, 2008) or increased (Hayase, 2007, 2008, 2011, 2013) depressive behavior with nicotine use.…”
Section: Discussionmentioning
confidence: 99%